CORRELATION OF PD-L1 GENE EXPRESSION WITH GRADE OF THE URINARY BLADDER CANCER - Stankov, Viktor; Stankov, Oliver; Dohchev, Sasho; Stavridis, Sotir; Ivanovski, Ognen; Janchulev, Josif; Ambardjieva, Martina; Gavrilovska-Brzanov, Aleksandra; Panov, Sasho; Saidi, Skender (Македонско лекарско друштво = Macedonian medical association, 2023)
Abstract Introduction. Bladder cancer (BC) ranks fourth in the prevalence of malignancies in developed countries and is the eighth leading cause of cancer-related mortality in men. PD-L1, known for its role in inhibiting immune responses against malignant cells, has garnered significant attention in BC research. Methods. This study, comprising 45 patients with histopathologically confirmed urothelial carcinoma of the urinary bladder, analyzed the connection between histological grade and PD-L1 gene expression. The patient cohort was divided into 31 classified as low-grade and 14 as high-grade, with gender and age distribution well-balanced across the groups. PD-L1 expression was notably higher in the high-grade group (p=0.005), showing its potential clinical relevance as a biomarker. Results. Univariate logistic analysis revealed a robust correlation between histological grade and PDL1 expression, with high-grade patients exhibiting a 7.227-fold higher likelihood of increased PD-L1 expression. A predictive model for grade determination demonstrated commendable performance, boasting an area under the curve (AUC) of 0.788. Conclusion. These findings provide compelling evidence of a strong association between PD-L1 gene expression and the histological grade of bladder cancer. PD-L1 emerges as a potential biomarker, shedding light on a disease pathological grade, offering a significant clinical value for precise prognosis, and guiding tailored treatment strategies. These insights hold promise for improved disease management and patient outcomes.
КОРЕЛАЦИЈА НА ЕКСПРЕСИЈАТА НА ГЕНОТ PD-L1 СО ГРАДУСОТ НА КАРЦИНОМОТ НА МОЧЕН МЕУР
Keywords: bladder cancer; PD-L1 gene expression; polymorphisms rs861539; biomarker